Assessment Act: Conserving Efficiency And Quality In Dental Practices Through Effective Dentist-Assistant Partnerships (Journal of Namibian Studies : History Politics Culture, 2022)
Achieving a balance between efficiency and quality is a central challenge for dental practices, and effective partnerships between dentists and assistants play a pivotal role in addressing this challenge. This article examines the strategies and best practices that dental teams can employ to optimize their collaboration, thereby enhancing both the efficiency of operations and the quality of patient care. By understanding the roles of dental assistants, fostering clear communication, delegating tasks appropriately, investing in training and continuing education, and providing regular performance evaluation and feedback, dental practices can achieve a harmonious balance between efficiency and quality. This balanced approach not only improves patient satisfaction but also contributes to the long-term success and sustainability of the practice.